Haste Makes Waste: Banking Organization Growth and Operational Risk - Frame, W Scott; McLemore, Ping; Mihov, Atanas (The Review of Corporate Finance Studies, 2026)
Abstract This study shows that higher banking organization growth is associated with higher operational losses per dollar of total assets and incidence of tail operational losses. Event studies using merger and acquisition activity and instrumental variable regressions provide consistent evidence. The relationship between banking organization growth and operational risk varies by loss event types and balance sheet categories. Higher growth before the Global Financial Crisis predicts higher operational losses during the crisis. We also find evidence that executive compensation incentives and board monitoring could moderate the relationship between growth and operational losses. These findings have implications for banking organization performance, risk management, and supervision as the banking industry continues to grow and consolidate.